Statins use is associated with poorer glycaemic control in a cohort of hypertensive patients with diabetes and without diabetes - Liew, Su May; Lee, Ping Yein; Hanafi, Nik Sherina Haidi; Ng, Chirk Jenn; Wong, Stalia Siew Lee; Chia, Yook Chin; Lai, Pauline Siew Mei; Mohd Zaidi, Nur Farhana; Khoo, Ee Ming (BioMed Central, 2014)
Background: The US Federal and Drug Administration (FDA) recently revised statin drug labels to include the information that increases in fasting serum glucose and glycated haemoglobin levels have been reported with the use of statins. Yet in a survey, 87% of the doctors stated that they had never or infrequently observed increases in glucose or HbA1c levels in patients on statin. In this study we would like to determine the association between the use of statins and glycaemic control in a retrospective cohort of patients with hypertension. Methods: A retrospective review of 1060 medical records of patients with hypertension at a primary care clinic was conducted. These records were selected using systematic random sampling (1:4). Data on patient socio-demographic factors; clinical profile; investigation results and prescribed medications were collected. Independent t-test was used for continuous variables while Pearson’s χ2 test was used for categorical variables. Logistic regression was done to adjust for confounders. Results: 810 (76.4%) patients with hypertension were on statins, out of which 792 (97.8%) were taking simvastatin 10 mg or 20 mg daily. Analysis of the whole group regardless of diabetes status showed that the statin user group had higher HbA1c and fasting blood glucose values. The difference in HbA1c levels remained significant (adjusted OR = 1.290, p = 0.044, 95% CI 1.006, 1.654) after adjustment for diabetes, diabetic medication and fasting blood glucose. In the study population who had diabetes, statin users again had significantly higher HbA1c level compared to statin non-users. This difference remained significant (adjusted OR 1.208, p = 0.037, 95% CI 1.012, 1.441) after adjustment for age and diabetic medications. Conclusions: Statins use is associated with increased HbA1c levels among hypertensive patients and hypertensive patients with diabetes. Clinicians managing hypertensive patients on statins should consider monitoring the HbA1c level and ensure that those with diabetes have their hyperglycaemia kept under control.